Bi-temporal processing in music notation reading: a theory linking prediction, memory, and automaticity - Heath, Karen L. (Frontiers in Cognition, 2026)
Reading music notation requires musicians to extract and interpret visual information in real time while simultaneously anticipating future performance actions. This dual engagement, in which one acts in the present while processing material to be performed in the future, suggests that music reading relies on a bi-temporal cognitive architecture. Grounded in this premise, this theoretical paper develops a model that integrates Hebbian learning and automaticity as core mechanisms supporting the simultaneous perceptual and anticipatory demands of notation-based music performance. A systematic review of neuroimaging studies involving music-reading tasks was conducted to evaluate current evidence on the neural correlates of notation processing. The results of the review showed that music reading engaged distributed cortical and subcortical networks, including regions commonly implicated in text reading, and recruited auditory-motor integration systems essential for music performance. However, most studies isolated single parameters of notation (e.g., pitch identification), thereby limiting ecological validity and constraining interpretations of how musicians process in real-world contexts that require concurrent multi-parameter integration. Complementary research on cognitive prediction, sensorimotor coupling, and perceptual-motor learning demonstrates that musicians employ a dual-pathway system of immediate perception and forward prediction, shaped by Hebbian synaptic strengthening and the development of automaticity through repeated procedural engagement. Synthesizing these findings, this article proposes a bi-temporal cognitive model of music-notation processing that accounts for dynamic interplay between associative learning, predictive processing, and automated motor execution. The implications of this model for cognitive theory and music pedagogy are discussed, with recommendations for empirical approaches to test the bi-temporal framework and advance understanding of real-time cognitive coordination in music performance.